Accounting theory - Riahi-Belkaoui, Ahmed (London : Thomson Learning, 2000)
The history and development of accounting. The nature and uses of accounting. The traditional approaches to the formulation of an accounting theory. The regulatory approach to the formulation of an accouting theory. A conceptual framework for financial accounting and reporting. The structure of accounting theory. Fairness, disclosure and future trends in accounting...
Keywords: Accounting; Accounting